Analytical imaging techniques for soft matter characterization - Mittal, Vikas (Engineering Materials, 2012)
This book describes the microscopic characterization of the soft matter in the light of new advances acquired in the science of microscopy techniques like AFM, SEM, TEM etc. The book does not focus on the traditional information on the microscopy methods as well as systems already present in different books, but intends to answer more fundamental questions associated with commercially important systems by using new advances in microscopy. Such questions are generally not answered by other techniques. The contents of the book also reflect this as the chapters are not based on describing material systems, but rather on the answering the problems or questions arising in their characterization. Both qualitative as well as quantitative analysis using such microscopic techniques are discussed. Moreover, the book has a broader reach as both polymers as well as biological matter have been included as different sections. Such a text with comprehensive overview of the various characterization possibilities using microscopy methods is currently not available in the market and can be a good reference book for microscopy experts as well as non-experts alike.